La danza folclórica en el desarrollo cultural en niños - Vizuete Valle, Anibal Humberto (2024)
The present title work entitled "Folk dance in cultural development in children" seeks to analyze the impact of folk dance on the cultural development of children from the fifth year of General Basic Education parallel "F" of the Educational Unit Juan de Velasco Sede 3 "Juan Bernardo de León" due to the devaluation that has been given to folk dance for the lack of knowledge of its pedagogical value. The methodology used was field, bibliographic, and worked with a quasi-experimental design, For the collection of information, student surveys were applied and previously validated by members of the career commission. The results showed that 87% have knowledge about folk dances in Ecuador while 13% do not know. 53% of students report not having received folk dance classes and 100% of students say that folk dance should be part of school education. In response to the problem studied, the "Kuntur Andino" Didactic Guide for Folk Dance was designed to strengthen the cultural development of children in general basic education; The training programme consists of a series of steps which will serve as support and guidance for teachers to carry out the corresponding activities, The latter are based on the skills under the performance criterion of the area of physical education for the level of basic general education. Finally, it is suggested that a dance school be created in this space for students who wish to receive more indepth and specialized training.